PIM studies inform Nigeria’s National Gender Policy in Agriculture - CGIAR Research Program on Policies, Institutions, and Markets (2019)
IFPRI’s support to Nigeria’s Federal Ministry of Agriculture and Rural Development on drafting the National Gender Policy on Agriculture started in 2016 and continued until the launch of the policy in October 2019. This policy is expected to enhance food security and accelerate development in Nigeria.